2011
DOI: 10.3727/096368910x557146
|View full text |Cite
|
Sign up to set email alerts
|

Novel Culture Technique Involving an Histone Deacetylase Inhibitor Reduces the Marginal Islet Mass to Correct Streptozotocin-Induced Diabetes

Abstract: Islet transplantation is limited by the difficulties in isolating the pancreatic islets from the cadaveric donor and maintaining them in culture. To increase islet viability and function after isolation, here we present a novel culture technique involving an histone deacetylase inhibitor (HDACi) to rejuvenate the isolated islets. Pancreatic islets were isolated from Sprague-Dawley (SD) rats and one group (FIs; freshly isolated islets) was used after overnight culture and the other group (RIs; rejuvenated islet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Enhancing effects of TSA on βTC-tet cells in this study are in accordance with reports of a dose-dependent increase in insulin secretion from human islets treated with VPA (10) and increased insulin secretion after the use of a culture technique on rat islets involving 0.1 μM TSA treatment for 24 hours (9). The effects of TSA alone on rat islets in the latter study, however, were not assessed and results from the former study were attributed to the structural similarity of VPA to free fatty acid secretagogues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Enhancing effects of TSA on βTC-tet cells in this study are in accordance with reports of a dose-dependent increase in insulin secretion from human islets treated with VPA (10) and increased insulin secretion after the use of a culture technique on rat islets involving 0.1 μM TSA treatment for 24 hours (9). The effects of TSA alone on rat islets in the latter study, however, were not assessed and results from the former study were attributed to the structural similarity of VPA to free fatty acid secretagogues.…”
Section: Discussionsupporting
confidence: 93%
“…As β-cell function is critical for proper blood glucose regulation, investigating direct HDACi effects on β-cell function is vital toward developing a clinically acceptable treatment. Some studies have observed HDACi effects on β-cell line or islet function, but as an aside to their primary investigation of anti-inflammatory effects (3, 4) or a pre-culture method for improved islet transplantation (9). So far, the reported effects have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to monitor, quantitatively, islet volume within encapsulation systems has been proposed as a method for tracking islet survival and function. 53,54 Our results suggest that further development of XPC for in vivo imaging could provide an important new tool for monitoring encapsulated islets.…”
Section: Discussionmentioning
confidence: 81%
“…53,54 Quantitative data can be extracted from the XPC mCT volume images, allowing determination of islet volume in the beads. The mean volume determined from XPC refraction images was 1.7 -0.08 · 10 5 mm 3 .…”
Section: Xpc Of Microbeads Preimplantationmentioning
confidence: 99%
“…HDAC6 inhibition by TSA or tubacin (an HDAC6 selective inhibitor) can also prevent ischemia and reperfusion-induced retinal neurodegeneration [246]. GLP-1 treatment has been reported to alleviate diabetic retinopathy by inhibiting hyperglycemia-provoked autophagy in the retina of T2D rats mediated through the restoration of GLP-1R expression and HDAC6 inhibition [247]. 5-aza-2'deoxycytidine and TSA, two pan-HDACis, were found to protect human retinal endothelial cells and retinal pigment epithelial cells from toxic effects of hyperglycemic stimuli in vitro by reciprocating high glucose-induced suppression of pigment epithelium-derived factor and counteracting with inflammatory factors [248].…”
Section: Hdac-mediated Therapeutic Options In Diabetic Retinopathymentioning
confidence: 99%